Correlation of Epidermal Fibroblast Growth Factor and Clinical Improvement of Asthma in Children after Zinc Supplementation - Retno Asih Setyoningrum; Anang Endaryanto; I Dewa Gede Ugrasena (Faculty of Medicine Universitas Airlangga, 2020)
Background: Background The presence of remodeling process on the pathogenesis of asthma that involves some growth factors such as epidermal growth factor (EGF) and fibroblast growth factor (FGF) causes the chronicity of the disease. The role of zinc on the pathogenesis of asthma is being widely investigated. This study aimed to analyze the correlation between EGF and FGF2 and clinical improvement of asthma after zinc supplementation.Methods: A quasi-experimental study was conducted in Outpatient Clinic Dr. Soetomo Hospital. The samples were persistent asthma patients from 6-15 years old who received controller therapy. The samples were divided into 2 groups, those who received zinc supplementation as the intervention group, and who received pacebo as the control. EGF and FGF2 plasma level of both groups were measured, and clinical improvement was evaluated with Childhood Asthma Control Test (C-ACT).Results: There were 11 patients who received zinc supplementation and 12 patients in the control group. There was a significant difference (p = 0.000) on the increase of EGF level in the intervention group (55.59 ± 6.48) than the control (5.35 ± 5.55). There was a significant difference (p = 0.000) on the increase of the FGF2 level in the intervention group (6.37 ± 1.41) than the control (0.72 ± 0.48). The increase of EGF (r = 0.592; p = 0.003) and FGF2 (r = 0.607; p = 0.002) would be followed by the increase of C-ACT scores.Conclusion: Zinc supplementation increase EGF and FGF2 levels. This improvement is correlated with clinical improvement of patients.